The Relationship Between the Utilization of the Maternal and Child Health (MCH) Handbook and Knowledge and Frequency of Antenatal Care (ANC) Visits at Candipuro Inpatient Health Center in 2025 - Sari, Yuni Maryana; Ermasari, Anissa; Kurniasari, Devi; Fitria, Fitria (JKM (Jurnal Kebidanan Malahayati), 2025)
Latar Belakang: Berdasarkan data rekam medis di Puskesmas Rawat Inap Candipuro tahun 2024 diketahui dari 1147 ibu hamil dengan kunjungan K1 sebesar 88,93%, K4 sebesar 81,26% dan K6 sebesar 71,3%. Keberhasilan program kesehatan ibu dapat dinilai melalui indikator utama Angka Kematian Ibu (AKI). Ibu hamil yang membaca buku KIA akan mengalami peningkatan pengetahuan dan kesadaran kesehatan.Tujuan: Tujuan penelitian diketahui hubungan pemanfaatan buku kesehatan ibu dan anak (KIA) Dengan pengetahuan dan frekuensi kunjungan antenatal care (ANC) di Puskesmas Rawat Inap Candipuro Tahun 2025Metode: Jenis penelitian ini adalah kuantitatif, rancangan penelitian cross sectional. Populasi dalam penelitian ini adalah seluruh ibu hamil di Wilayah Kerja Puskesmas Rawat Inap Candipuro sebanyak 68 ibu hamil dengan sampel yang digunakan sebanyak 54 responden, meggunakan teknik acidental sampling. Pengumpulan data menggunakan lembar kuesioner, analisis data secara univariat dan bivariat (uji chisquare).Hasil: Hasil penelitian diketahui bahwa sebanyak 28 (51,9%) responden memanfaatkan buku KIA, sebanyak 35 (64,8%) responden memiliki pengetahuan baik, dan sebanyak 30 (55,6%) responden melakukan kunjungan ANC tidak sesuai.Kesimpulan: . Ada hubungan pemanfaatan buku KIA dengan pengetahuan ibu hamil (p-value =0,013) dan hubungan pemanfaatan buku KIA dengan frekuensi kunjungan ANC pada ibu hamil (p-value =0,00) di Puskesmas Rawat Inap Candipuro tahun 2025.Saran: Saran bagi Ibu hamil diharapkan dapat memanfaatkan Buku KIA dengan membaca isinya secara rutin dan membawanya saat kunjungan ANC sebagai sumber informasi dan pencatatan kesehatan kehamilan. Kata Kunci: frekuensi kunjungan ANC, Ibu hamil, pemanfaatan buku KIA, pengetahuan ABSTRACT Background: Based on medical records at Candipuro Inpatient Health Center in 2024, out of 1,147 pregnant women, the percentage of K1 visits was 88.93%, K4 visits was 81.26%, and K6 visits was 71.3%. The success of maternal health programs can be assessed through a key indicator, the Maternal Mortality Rate (MMR). Pregnant women who read the Maternal and Child Health (MCH) Handbook are expected to experience an increase in knowledge and health awareness.Purpose This study aimed to determine the relationship between the utilization of the Maternal and Child Health (MCH) Handbook and knowledge as well as the frequency of antenatal care (ANC) visits at Candipuro Inpatient Health Center in 2025.Methods: This was a quantitative study with a cross-sectional design. The population consisted of all pregnant women in the working area of Candipuro Inpatient Health Center, totaling 68 women, with a sample of 54 respondents selected using accidental sampling. Data were collected using questionnaires and analyzed through univariate and bivariate analyses (Chi-square test).Results: The results showed that 28 respondents (51.9%) utilized the MCH Handbook, 35 respondents (64.8%) had good knowledge, and 30 respondents (55.6%) had ANC visits that were not in accordance with the recommended schedule.Conclusion: There was a significant relationship between the utilization of the MCH Handbook and maternal knowledge (p-value = 0.013), as well as between the utilization of the MCH Handbook and the frequency of ANC visits among pregnant women (p-value = 0.00) at Candipuro Inpatient Health Center in 2025.Suggestion: Pregnant women are encouraged to make use of the MCH Handbook by regularly reading its contents and bringing it during ANC visits as a source of information and a record of maternal health. Keywords: ANC visit frequency, pregnant women, utilization of the MCH Handbook, knowledge